Homotopy Perturbation Method for Solving Fokker-Planck Equation - M. Khudhir , Jehan (University of Thi-Qar Journal of Science, 2019)
In this paper, linear and nonlinear Fokker-Planck equations and some similar equations by usinghomotopy perturbation method are solved. Some examples are solved by homotopy perturbation method to illustrate the simplicity and reliability of this method.